Impacts of smoking on alcoholic liver disease: a nationwide cohort study - Yoo, Jeong-Ju; Lee, Dong Hyeon; Kim, Sang Gyune; Jang, Jae Young; Kim, Young Seok; Kim, Log Young (Frontiers in Public Health, 2024)
Objectives Smoking is a preventable risk factor for morbidity and mortality in patients with liver disease. This study aims to explore the additional risks of smoking in the development of alcoholic liver disease (ALD), cirrhosis, and hepatocellular carcinoma (HCC) in high-risk drinkers. Methods Data from the National Health Insurance Service, including claims and health check-up information spanning 2011 to 2017, were used. The overall alcohol consumption was calculated, and ALD was defined based on ICD-10 codes. High-risk drinking was defined as 7 or more drinks for men and 5 or more for women, twice weekly. Half of the high-risk drinkers were smokers, decreasing in men but stable at 20% for women. Results ALD prevalence was 0.97% in high-risk drinkers and 1.09% in high-risk drinkers who smoked, higher than 0.16% in social drinkers (p < 0.001). ALD incidence over 3-years was highest in high-risk drinkers who smoked (2.35%), followed by high-risk drinkers (2.03%) and social drinkers (0.35%) (p < 0.001). Cirrhosis and HCC followed similar patterns, with prevalence and incidence was highest in drinkers who smoked. 3-year mortality was 0.65% in high-risk drinkers who smoked, compared to 0.50% in high-risk drinkers and 0.24% in social drinkers (p < 0.001). Smoking increased the incidence of ALD, cirrhosis, and HCC by 1.32, 1.53, and 1.53 times, respectively (all p < 0.001). Gender-specific analysis revealed higher risk ratios (RR) for women in ALD, alcoholic cirrhosis, and HCC, particularly among high-risk drinkers who smoked. Women showed significantly increased RR in ALD (6.08 to 12.38) compared to men (4.18 to 4.40), and similar trends were observed for cirrhosis and HCC. Conclusion Smoking significantly heightens the risk of ALD, cirrhosis, and HCC, especially in women, among high-risk drinkers. This emphasizes the importance of smoking cessation, particularly for female patients with ALD.